An assessment of climate variation risks on agricultural production: Perceptions and adaptation options in Benin - TEKA, SEMADEGBE OSCAR; Houessou, Laurent G; OUMOROU, ALIOU ABOUDOU MADJIDOU; Vogt, Joachim; SINSIN, AUGUSTIN BRICE (My University, 2013)
Purpose – The purpose of this paper is to assess the local communities’ perception of climate variation effects on crop production and the adopted strategies by farmers in order to cope with the negative effects of climate on the agriculture in the coastal zone of Benin. Design/methodology/approach – A total of 290 agricultural households were sampled and surveyed through structured interviews. The principal component analysis (PCA) was performed on the relative frequencies citation of perceived climate variation indication in order to describe the relationship between risk perceptions according to socio-demographic characteristics. The relative frequency of citation was calculated according to age, gender, ethnic group and agro-ecological region. Findings – Results showed that almost 83 per cent of the respondents already perceived the climate change risks through several indications. Climate variation perception varied with respect to age. Respondents’ opinion regarding climate variation causes depended generally on their age, religion and level of education. As far as climate variation risks impact on crop production is concerned, the respondents’ opinions diverged. Originality/value – The assessment of local communities’ perception is important to design participatory and sustainable measures to cope with harmful effects of climate variation on crop production.
Keywords: Climate variation; Crop production; Perception; Adaptation; Tradition; Benin